SCREENING FOR METHICILLIN RESISTANT Staphylococcus Aureus FROM HANDS, KNIVES AND TABLES OF MEAT AND MEAT PRODUCTS VENDORS IN SOME SELECTED AREAS IN KANO, NIGERIA - SHAMSUDDEEN, U; DAHIRU A. T; PUMA H. U (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
A total of 120 swab samples of hands, knives and tables of Fresh meat, Balangu, Kilishi and Tsire vendors were investigated for the presence of Methicillin Resistant Staphylococcus aureus (MRSA). Samples were randomly taken using sterile swab stick at different retailing points within the local governments constituting Kano Metropolis. Staphylococcus aureus isolates were isolated using mannitol salt agar. Identification of isolates was done using biochemical tests. From the 120 swab samples analyzed, 12 S. aureus isolates were detected. Out off the 12 isolates, 6(50%) were from the hands of the vendors, 2(16.67%) from knives and 4(33.33%) were from tables. The isolated organisms were subjected to sensitivity tests using clinical laboratory standards Institute (CLSI) break point procedure. Only 8% out of the 12 S. aureus isolates was confirmed MRSA positive but with no statistical significant difference at P- value 95% in the occurrence rate of MRSA among the samples. This is a challenge to public health policy makers in the state.